Les conceptions chinoises en matière de relations internationales - Engelborghs-Bertels, Marthe (Études internationales, 1981)
The author identifies the variations in Peking's foreign policy since 1949 as the variable outcome of an equation involving stable principles and changing contexts. First, she identifies those principles that from the Chinese perspective are the guidelines of their foreign policy. Second, she attempts to demonstrate by reference to practice that these principles, far from constituting restrictive norms, are adapted to situations in a manner to ensure the perpetuity of China. Informed by an ages-old diplomatic tradition, the essentially pragmatic Chinese leadership interpret changes in the international context in the light of long-term objectives. These may be summarized by two concepts : the safeguarding of peace and the emancipation of humanity. By taking these considerations into account the author studies the foreign policies of the Chinese People's Republic that would appear to be the most susceptible of demonstrating the conceptions of its leaders with respect to international relations. In particular, the strategic position of the China of the 80s is commented upon within this analytical framework. The author concludes from her observations that Chinese behaviour on the international scène may be better understood by considering the goals pursued rather than the statements of principles put forward.